Look Back: The feds, the states, and Kappan. (October 2019) - Preston, Teresa
Across the decades, the balance of power between the federal government, states, and local districts has shifted numerous times, and Kappan authors have weighed in on each of those shifts. Kappan Managing Editor Teresa Preston traces those shifts, beginning with the 1965 Elementary and Secondary Education Act (ESEA), which gave the federal government a larger role in public education. Further expansion occurred under the Carter administration, with the launch of the new federal Department of Education. As the new department continued operations under Reagan, its priorities expanded, but actual decision-making authority reverted to states. States, in turn, began involving themselves more with instructional and curricular matters, a trend that eventually made its way back to the federal level, with the passage of the No Child Left Behind Act (NCLB). Under NCLB, federal mandates had the effect of requiring state and local levels to take on additional responsibilities, without necessarily having the capacity to do so. This capacity issue remains a concern under the Every Student Succeeds Act (ESSA) .